2020
DOI: 10.1002/bit.27495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glutathione proteome in CHO cells and its relationship with productivity and cholesterol synthesis

Abstract: Glutathione (GSH) plays a central role in the redox balance maintenance in mammalian cells. Previous studies of industrial Chinese hamster ovary cell lines have demonstrated a relationship between GSH metabolism and clone productivity. However, a thorough investigation is required to understand this relationship and potentially highlight new targets for cell engineering. In this study, we have modu-This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Our data compares favorably with Turan et al 57 MSX inhibits the activity of the enzyme GCL, which catalyzes the synthesis of reduced glutathione (GSH) from its precursor amino acids: glutamic acid, cysteine, and glycine. 59 Alteration in the amount of glutathione (either GSH or GSGG forms) has been shown to have dramatic consequences on productivity 39,60,61 and oxidative status 62 in RI derived cell lines.…”
Section: Product Quality For Mabs Produced From the Hd7876 Hostmentioning
confidence: 99%
“…Our data compares favorably with Turan et al 57 MSX inhibits the activity of the enzyme GCL, which catalyzes the synthesis of reduced glutathione (GSH) from its precursor amino acids: glutamic acid, cysteine, and glycine. 59 Alteration in the amount of glutathione (either GSH or GSGG forms) has been shown to have dramatic consequences on productivity 39,60,61 and oxidative status 62 in RI derived cell lines.…”
Section: Product Quality For Mabs Produced From the Hd7876 Hostmentioning
confidence: 99%
“…However, overexpression of the catalytic subunit of γ-glutamyl cysteine synthetase (GCL, the bottleneck enzyme in GSH biosynthesis) in CHO cells, which led to an increased intracellular concentration of GSH, did not improve the production of a monoclonal antibody in transient expression assays [ 67 ]. A subsequent study of a monoclonal antibody-producing CHO cell line where its GSH content was down-modulated by limiting cysteine supply or by chemical inhibition of GCL has shown a severe impairment in the productivity of the heterologous protein [ 68 ]. The parallel proteomic analysis conducted in this study further revealed additional metabolic adaptations of the cells in response to GSH depletion that involved the downregulation of a subset of glutathione S-transferase enzymes, TCA-cycle enzymes, and lipid biosynthesis (cholesterol in particular), and the upregulation of several antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The protein samples were prepared according to Chevallier et al [ 47 ]. P. rubra S4059 wild type and GH19 mutant were grown in 20 mL MMM with crystalline chitin for 2 days at 25 °C, 200 rpm.…”
Section: Methodsmentioning
confidence: 99%